Analisis Perbedaan Pengaruh Kepuasan terhadap Kepercayaan dan Loyalitas Pasien - Raditya Sukmana; Ririn Tri Ratnasari (Telaah Bisnis, 2016)
Abstract This study aims to determine that the effect on patient satisfaction and patient trust in RSI and RKZ. Effect on patient satisfaction and loyalty in RKZ and RSI, and patients’ trust effect on patient loyalty in RSI and RKZ. The approach will be used for this research is a quantitative research approach. The population in this study were patients who take medication and inpatient treatment at the Islamic Hospital and in RKZ Vincent’s Hospital for more than 1 (one) week in the period June to August. The number of total sample of 100 patients, divided into two, namely 50 Islamic Hospital patients and 50 patients in RKZ Vincent Hospital. The way sampling is purposive sampling. The analysis technique used in this research is path analysis.These results indicate that the effect on patient satisfaction and patient trust in RSI and RKZ. Effect on patient satisfaction and loyalty in RKZ and RSI, and patients’ trust effect on patient loyalty in RSI and RKZ. Suggestions for the management of Islamic Hospital, should have to pay attention to the complaints of patients and the need to respond quickly to patient complaints regarding jenguk limited hours and take turns. For further research, research must be done by inserting a variable level of knowledge of religion and gender as a moderator variable.